2022
DOI: 10.1186/s12879-022-07559-0
|View full text |Cite
|
Sign up to set email alerts
|

Syndromic surveillance of respiratory-tract infections and hand hygiene practice among pilgrims attended Hajj in 2021: a cohort study

Abstract: Background The risk of transmission of viral respiratory tract infections (RTIs) is high in mass gatherings including Hajj. This cohort study estimated the incidence of symptomatic RTIs and hand hygiene compliance with its impact among Hajj pilgrims during the COVID-19 pandemic. Methods During the week of Hajj rituals in 2021, domestic pilgrims were recruited by phone and asked to complete a baseline questionnaire. Pilgrims were followed up after s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
0
5
1
Order By: Relevance
“…However, a cohort study during the same Hajj year showed greater prevalence rates of syndromic RTIs: 4.7% of the cohorts experienced RTI symptoms, and, respectively, 1.1% and 0.9% were suspected of having ILI and COVID-19. These lower rates were observed in this survey despite fewer pilgrims having university-level or higher education than those in the previous study (58.2% vs. 76.5%), and fewer were vaccinated against influenza (48.7% vs. 58.2%) and COVID-19 (88.7% vs. 92.5%) [15]. In contrast, previous studies found that the level of education was associated with higher compliance with preventive measures [21][22][23].…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…However, a cohort study during the same Hajj year showed greater prevalence rates of syndromic RTIs: 4.7% of the cohorts experienced RTI symptoms, and, respectively, 1.1% and 0.9% were suspected of having ILI and COVID-19. These lower rates were observed in this survey despite fewer pilgrims having university-level or higher education than those in the previous study (58.2% vs. 76.5%), and fewer were vaccinated against influenza (48.7% vs. 58.2%) and COVID-19 (88.7% vs. 92.5%) [15]. In contrast, previous studies found that the level of education was associated with higher compliance with preventive measures [21][22][23].…”
Section: Discussioncontrasting
confidence: 77%
“…Data are scarce on the post-Hajj prevalence of RTIs, and to the best of our knowledge, no study has assessed the prevalence of symptomatic RTIs among pilgrims during Hajj amidst the COVID-19 pandemic. A study conducted by our team during the peak period of Hajj in 2021 demonstrates the need for a post-Hajj surveillance study [15]. To this end, this manuscript aims to report the point prevalence of syndromic RTIs among domestic Hajj pilgrims who returned home after the pilgrimage in 2021 and assesses the risk of RTIs among pilgrims' contacts.…”
Section: Introductionmentioning
confidence: 99%
“…Crowding and a variety of health risks, such as trauma and injury, can render MGs dangerous [ 1 , 3 , 5 ]. Additionally, the high concentration of people at specific locations for a set period increases the risk of spreading infectious diseases, including viral respiratory tract infections [ 3 , 4 , 8 ]. To control and prevent pulmonary system infections during MG events, regularly practicing proper hand hygiene (HH) is highly advised [ 3 , 4 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the high concentration of people at specific locations for a set period increases the risk of spreading infectious diseases, including viral respiratory tract infections [ 3 , 4 , 8 ]. To control and prevent pulmonary system infections during MG events, regularly practicing proper hand hygiene (HH) is highly advised [ 3 , 4 , 8 ]. Good HH practice is considered one of the most effective strategies to halt the spread of infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Participatory surveillance enhanced through utilization of digital technologies during mass gatherings has been demonstrated during the 2014 FIFA World Cup [ 9 ] and 2016 Olympic Games [ 10 ]. Following the COVID-19 pandemic, syndromic surveillance for respiratory tract infections was conducted among pilgrims who attended Hajj in 2021 [ 11 ].…”
Section: Introductionmentioning
confidence: 99%